Clitoral epidermoid cyst secondary to blunt trauma in a 9-year-old child - Celik, Neslihan; Yalçin, Sule; Güçer, Safak; Karnak, Ibrahim (The Turkish Journal of Pediatrics, 2011)
Epidermoid cysts are slowly growing tumors arising from invagination of the epidermis into the dermis traumatically or spontaneously. This implantation in the clitoris is most commonly induced by female genital mutilation. The reported cases with spontaneous onset of this clitoral lesion are scarce. Trauma other than female circumcision predisposing to the onset of the cyst has not been mentioned before. A nine-year-old girl was presented for swelling in the pubic region with the onset following an accidental trauma; the diagnosis was determined to be epidermoid cyst of the clitoris after a brief preoperative evaluation and an accurate surgical management.